Pinto fires and personal ethics: A script analysis of missed opportunities - Gioia, Dennis A. (Journal of business ethics, 1992)
This article details the personal involvement of the author in the early stages of the infamous Pinto fire case. The paper first presents an insider account of the context and decision environment within which he failed to initiate an early recall of defective vehicles. A cognitive script analysis of the personal experience is then offered as an explanation of factors that led to a decision that now is commonly seen as a definitive study in unethical corporate behavior. The main analytical thesis is that script schemas that were guiding cognition and action at the time precluded consideration of issues in ethical terms because the scripts did not include ethical dimensions.